Palmatine Attenuates Metastatic Lung Colonization of Triple Negative Breast Cancer Cells - Ativui, Selase; Danquah, Cynthia A.; Ossei, Paul Poku Sampene; Ofori, Michael (Frontiers in Pharmacology, 2022)
Background Circulating tumor cells have a key role in the metastatic spread of breast cancer to the lungs via the lymphatic or circulatory system. Metastatic breast cancer remains incurable. Alkaloids extracted from medicinal plants exhibit antimetastatic and antiproliferative effects on triple negative breast cancers. This study thus investigated the inhibitory activity of palmatine, a natural alkaloid on the metastatic colonization of triple negative breast cancer cells in the lungs. Methods 4T1 triple breast cancer cells were transplanted synergically to the thoracic duct of female balb/c mice via the lymphatic system. Palmatine 1, 5 and 10 mg/kg were administered for 28 days. The lungs were analyzed for levels of arterial blood gas, histological damage, immunohistochemical expression of the metastasis-associated protein 1 (MTA1) and tumor suppressor p53 (p53). Results Administering palmatine 1-10 mg/kg dose dependently improved hypoxemia, ameliorated metastasis associated lung injury; histology score of 3.33 ± 0.33, 1.67 ± 0.33, 1.33 ± 0.33, decreased lung MTA1 (2.19 ± 0.12, 1.83 ± 0.04, 1.84 ± 0.05) and increased p53 expression (1.99 ± 0.06, 2.27 ± 0.12, 2.34 ± 0.12) respectively. Conclusion Palmatine preserved lung morphology and demonstrated therapeutic potential in aiding treatment of lung metastasis.